Corticosteroid-depending effects on peripheral immune cell subsets vary according to disease modifying strategies in multiple sclerosis - Höpner, Lena; Proschmann, Undine; Inojosa, Hernan; Ziemssen, Tjalf; Akgün, Katja (Frontiers in Immunology, 2024)
Background: The primary treatment for acute relapses in multiple sclerosis (MS) is the intravenous administration of high dose methylprednisolone (IVMP). However, the mechanisms through which corticosteroid treatment impacts acute neuroinflammation in people with MS (pwMS) remain not fully understood. In particular, the changes induced by glucocorticoids (GCs) on cells of the innate immune system and the differences between patients with distinct immunotherapies have received little attention to date. Methods: We conducted immunophenotyping using flow cytometry on peripheral blood mononuclear cells of pwMS who received IVMP treatment during a relapse. We compared the impact of an IVMP treatment on a broad variety of immune cell subsets within three groups: twelve patients who were treatment-naïve to disease modifying therapies (wDMT) to ten patients on platform therapies (PT) and eighteen patients on fingolimod therapy (FTY). Results: We observed pronounced interindividual short- and intermediate-term effects of IVMP on distinct immune cells subsets. In addition to the well-documented decrease in T-helper cells (Th cells), we detected significant alterations after the first IVMP infusion within the innate immune response among neutrophil, eosinophil and basophil granulocytes, monocytes and plasmacytoid dendritic cells (pDCs). When comparing patients wDMT to the PT and FTY cohorts, we found that IVMP had a similar impact on innate immune cells across all treatment groups. However, we did not observe a significant further decline in T lymphocyte counts during IVMP in patients with pre-existing lymphopenia under FTY treatment. Although T cell apoptosis is considered the main mechanism of action of GCs, patients with FTY still reported symptom improvement following IVMP treatment. Conclusion: In addition to T cell suppression, our data suggests that further immunoregulatory mechanisms of GC, particularly on cells of the innate immune response, are of greater significance than previously understood. Due to the regulation of the adaptive immune cells by DMTs, the impact of GC on these cells varies depending on the underlying DMT. Additional studies involving larger cohorts and cerebrospinal fluid samples are necessary to gain a deeper understanding of the immune response to GC in pwMS with different DMTs during relapse to define and explain differences in clinical response profiles.